Prevalence of Temporomandibular Joint Disorders and its Association with Para Functional Habits in the Patients Attending Tertiary Care Hospital - Chaulagain, Rajib; Maharjan, Anjana (Journal of Nepal Health Research Council, 2019)
Background: Temporo-mandibular disorders is a collective term used to describe problems involving muscles of mastication and temporomandibular joint. The study aimed to evaluate the prevalence of temporo-mandibular disorders and its association with parafunctional habits in patients visiting department of dentistry, Patan Academy of Health Sciences.Methods: A cross-sectional study was carried out among 213 patients coming to Patan Academy of Health Sciences. A screening questionnaire recommended by American Association of Orofacial Pain was used to determine the signs and symptoms of temporo-mandibular disorders.Results: The prevalence of temporomandibular disorders was 31.9 %. The three most common parafunctional habits were chewing gums (32.4 %), mouth breathing (19.7 %) and biting of objects (14.6 %) respectively. Statistically significant association was found between nail biting, grinding of teeth, biting of lips and objects and mouth breathing with signs and symptoms of temporomandibular disorders (p<0.05). Among the signs and symptoms of temporomandibular disorders, getting headaches, neck pain or toothaches often was the most frequent signs of temporomandibular disorders (n=105, 49.3 %). Feeling of recent change in bite was the second most frequent sign reported by 82 participants (38.5 %).Conclusions: The parafunctional habits between nail biting, grinding of teeth, biting of lips and objects and mouth breathing have statistically significant association with signs and symptoms of temporomandibular disorders. Keywords: AAOP; parafunctional habits; prevalence; TMDs.